Soviet Mobilisation of Handicraft Industry during the Civil War (Based on the Materials of Tambov Province) - Valery Vladimirovich Kanishchev; Georgiy Sergeevich Makhrachev (Известия Уральского федерального университета. Серия 2: Гуманитарные науки)
This study is devoted to the mobilisation of small producers by the Soviet authorities to solve state tasks in a crisis period of history, during the years of the civil war. The article reveals the implementation of state orders. During the first stages of the Soviet state, the issues of handicraft production fell under the jurisdiction of the Supreme Council of National Economy and the People’s Commissariat for Agriculture, and more particularly, their local departments. The unsatisfactorily organised work of these agencies was aggravated by the desire of local governments to attract craftsmen to solve their own problems. There was no control over the volume of orders and budgets, which led to the emergence of false cooperatives, exploitation of craftsmen, and inflated prices for final products. The Soviet government attempted to regulate the process of engaging craftsmen in the fulfilment of state orders by transforming the structures in charge of these issues several times. In practice, this led to an even greater disorganisation. Moreover, local authorities could not keep up with the huge number of new decrees coming from the top. The situation was made worse by irregularities in the provision of materials, tools, and financing to craftsmen. As a result, in order to win the civil war, the Soviet government made a radical decision to move to the direct mobilisation of artisans who, in a situation of complete economic decline, were ready to work in any conditions. As a result, by the end of “war communism’” the most widespread types of small-scale production were those related to military needs.